HUBUNGAN KELINCAHAN DAN KELENTURAN DENGAN KEMAMPUAN DRIBBLING SEPAKBOLA TIM SMAN 1 SEDINGINAN KECAMATAN TANAH PUTIH - Yusnita '; Ramadi '; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this research is the lack of soccer dribbling skills that owned the team SMAN 1 Sedinginan. From experiments in breaking through the opponent's defense looks still many players who are less good at doing dirbbling so easy to move the ball with mastery. This problem can be seen from the observation of researcher during a friendly match, it is suspected because of the agility and flexibility that is owned by the player. Therefore, the purpose of this study was to determine whether there is a corealtion the agility and flexibility with football dribbling ability of the team SMAN 1 Sedinginan. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As independent variables (X1) is agility, (X2) flexibility while the dependent variable (Y) is a soccer dribbling skills. This research data obtained from the test results using zig-zag run test, sit and reach test and dribbling ability test. The sample in this study is a soccer player team SMAN 1 Sedinginan amounting to 23 people (total sampling). Based on the research results can be concluded as follows: There is a significant corelation between agility on the dribbling ability, where rtab at significant level α (0,05) = 0.413 means rhitung (0.49)> rtab (0.413). There is a significant corelation between flexibility on the dribbling ability, where rtab at significant level α (0,05) = 0.413 means rhitung (0.44)> rtab (0.413). There is a significant corelation together between agility and flexibility in the dribbling ability of Tim Sedinginan SMA Negeri 1 Tanah Putih, where rtab at significant level α (0,05) = 0.413 means rhitung (0.58)> rtab (0.413) ,Keywords : Agility, Flexibility, Dribbling, Soccer